Active and Passive Smoking in Adults Undergoing a Long-Term Multi-Setting Healthy Lifestyle Education: Tehran Lipid and Glucose Study. (March 2023) - Masihay-Akbar, Hasti; Amiri, Parisa; Cheraghi, Leila; Momenan, Amir Abbas; Azizi, Fereidoun
We aimed to investigate the effects of a multi-setting lifestyle education on men's cigarette, hookah, and passive smoking, and women's passive smoking, in Iran. Data of Tehran Lipid and Glucose Study (TLGS) were used. TLGS started in 1999 with every-3-year follow-ups. Multi-stage cluster random sampling was used to recruit participants under the coverage of three health centers. One health center implemented multi-setting lifestyle education at school, family, and community setting. Our analytic sample for generalized estimating equation was restricted to 1322 and 3593 adults (respectively as intervention and control) who were followed for 15.8 years. Intervention reduced the odds of men's cigarette smoking by 27%. The estimated mean cigarettes/day was 1.58 lower in intervention men. The intervention reduced the odds of men's hookah use by 42% in short term. Intervention women had 33% lower odds of passive smoking. Lifestyle education with community outreach can help achieve pragmatic tobacco control goals.